Electronic and magnetic properties of ternary sulfide Rb2Mn3S4 - Acharya, Gang Bahadur; Prasad Ghimire, Madhav (Himalayan Physics, 2023)
Semiconducting materials, especially with a direct band gap, are helpful for modern photovoltaic and optoelectronic device fabrication. Here, based on density functional theory calculations, we predict the electronic and magnetic properties of Rb2Mn3S4 by using the full potential local orbital code. Considering different configurations such as nonmagnetic, ferromagnetic, ferrimagnetic, and antiferromagnetic, the magnetic ground state was found to be ferrimagnetic with the lowest total energy. The calculated effective magnetic moment is 10μBunit cell (two formula units) resulting from the opposite spin interaction between Mn (I) and Mn (II) atoms in Rb2Mn3S4. From our calculations, Rb2Mn3S4 is found to be a semiconductor with a direct energy band gap of 0.75 eV. With the inclusion of the Coulomb interaction (i.e., GGA+U), the band gap is found to rise to 2.34 eV for U = 4 eV.